Knowledge, Attitude, Practices Related To Dengue Fever Among Rural Population In Terengganu, Malaysia - Myat Moe Thwe, Aung; Arunodaya, Barman; Norizhar, Kadarman (Malaysian Public Health Physicians Association, 2016)
Aedes mosquito-borne Dengue morbidity is predominantly high in the tropics and subtropics regions. Dengue is also a public health problem in Malaysia since the first epidemic in 1973. Reducing the vector population and personal protection still plays an important role in dengue prevention and control. With the information of community’s dengue knowledge, attitude and practices (KAP), the authorities could construct evidence-based, community- empowered vector control program. Upon the understanding of the value of baseline data, a cross-sectional study was carried out in dengue hotspot areas in Seberang Takir using universal sampling. The study results showed that 54.6% of the population had high level of knowledge, 18.6% had good attitude and 91.7% were performing good practices against Dengue infection. After adjusting confounding variables, age and educational levels of respondents, knowledge as well as attitude were found to be significant associated factors for having good practice against Dengue. The study findings provide the need for further information to undertake a holistic approach which is in need of community participation and cooperation.